All Days 2006
DOI: 10.2118/106361-ms
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Technique for Screening Asphaltene Inhibitors for Kuwaiti Reservoirs

Abstract: Currently Kuwait Oil Company (KOC) is facing asphaltene deposition problems in the wellbore of some of the Marrat Jurassic reservoirs in West Kuwait (WK) and South East Kuwait (SEK). This has caused a reduction in production and shutting of some of the wells and a severe detrimental effect on the economics of oil recovery. This paper describes the results of the laboratory studies on the characterization and phase behavior studies of three different crude oil samples from Marrat reservoirs, and the screening o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…13 Recently, researchers used experimental techniques to select the most effective inhibitor for their target asphaltene and petroleum cases. For instance, Oskui et al 14 screened the efficiency of three commercial inhibitors (named A-C) on three oil samples using asphaltene flock point analysis (titration technique). They demonstrated that Inhibitor B was effective in a range of concentrations (0.1−5%) for two oil samples, while Inhibitor A was effective for the third oil sample.…”
Section: Introductionmentioning
confidence: 99%
“…13 Recently, researchers used experimental techniques to select the most effective inhibitor for their target asphaltene and petroleum cases. For instance, Oskui et al 14 screened the efficiency of three commercial inhibitors (named A-C) on three oil samples using asphaltene flock point analysis (titration technique). They demonstrated that Inhibitor B was effective in a range of concentrations (0.1−5%) for two oil samples, while Inhibitor A was effective for the third oil sample.…”
Section: Introductionmentioning
confidence: 99%
“…Asphaltenes are a solubility class of crude oil and are defined as the fraction of crude oil that is soluble in aromatic liquids (e.g., toluene) and insoluble in normal alkanes (e.g., n -heptane). , Changes in the temperature, pressure, or composition may reduce asphaltene solubility within crude oil and, consequently, cause deposition in subsea wells, pipelines, and porous formations, resulting in potential losses of millions of dollars . In particular, wellbore deposition causes drops in production rates, and excessive fouling may require complete shut-in of the well, resulting in losses of up to 50 000 bbl/day. , Furthermore, the mixing of incompatible oil in a refinery can lead to asphaltene fouling of heat exchangers and other equipment . To reduce the extent of asphaltene deposition, a variety of techniques have been commercially employed, which include monitoring of thermodynamic parameters within wells to avoid conditions where asphaltene precipitations is induced and the use of chemical inhibitors. ,,, A classical mechanism of chemical inhibition is that inhibitors adsorb on asphaltene molecules/aggregates and form a steric stabilization layer that promotes asphaltene dispersion within crude oil solution; however, extensive assessment of inhibitor mechanisms of action has not been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, wellbore deposition causes drops in production rates, and excessive fouling may require complete shut-in of the well, resulting in losses of up to 50 000 bbl/day. , Furthermore, the mixing of incompatible oil in a refinery can lead to asphaltene fouling of heat exchangers and other equipment . To reduce the extent of asphaltene deposition, a variety of techniques have been commercially employed, which include monitoring of thermodynamic parameters within wells to avoid conditions where asphaltene precipitations is induced and the use of chemical inhibitors. ,,, A classical mechanism of chemical inhibition is that inhibitors adsorb on asphaltene molecules/aggregates and form a steric stabilization layer that promotes asphaltene dispersion within crude oil solution; however, extensive assessment of inhibitor mechanisms of action has not been reported in the literature. Inhibitor action is also highly specific to a number of conditions: oil properties, concentration of inhibitor, temperature of operation, etc .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The asphaltene onset pressure (AOP) is one of the most important factors in understanding asphaltene precipitating behavior. The solid detection system (SDS) based on light-scattering technique has been quite popular and widely used in all over the world (Kokal et al 2003(Kokal et al , 2004Jamaluddin et al 2000;Negahban et al 2005;Gholoum et al 2003;Garcia et al 2001;Oskui et al 2006;Gonzalez et al 2007) to measure AOP. The simple experiments to measure AOP are usually conducted using a mixture of reservoir fluid and injection gas, and various gas-mixing volumes are assumed to be investigated.…”
mentioning
confidence: 99%